2012
DOI: 10.1007/s11255-012-0314-x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of outcomes after resection of renal cell carcinoma with venous involvement

Abstract: Tumor thrombus level does not predict recurrence or mortality in RCC with venous involvement. Survival is determined by inherent aggressiveness of the cancer manifested by tumor size, grade and distant metastasis at presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 26 publications
2
26
0
2
Order By: Relevance
“…Some studies have found that extent of vena caval invasion was an important prognostic factor and that in majority of patients with positive vascular wall margins have increased recurrence rate (Abel et al, 2013). While according to some authors, survival is determined by the inherent aggressiveness of the cancer and that tumor thrombus level does not predict recurrence or mortality (Sidana et al, 2012). In our study, 10% (5/50) cases showed renal vein invasion.…”
Section: Discussionmentioning
confidence: 42%
“…Some studies have found that extent of vena caval invasion was an important prognostic factor and that in majority of patients with positive vascular wall margins have increased recurrence rate (Abel et al, 2013). While according to some authors, survival is determined by the inherent aggressiveness of the cancer and that tumor thrombus level does not predict recurrence or mortality (Sidana et al, 2012). In our study, 10% (5/50) cases showed renal vein invasion.…”
Section: Discussionmentioning
confidence: 42%
“…Main surgical access in patients with extended thrombus was median incision (47.4 %). To date, in cases when thrombus level extends the intra-and suprahepatic section of the IVC, surgery is associated with acceptable perioperative morbidity and mortality rates (Clavien classification ≥IV) [6][7][8]. Recent studies show lower mortality and perioperative complications compared with those from the 1970s to 1990s [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Several clinicopathological risk factors increasing disease-associated mortality are described. Diverse studies showed metastatic disease [3,5,6,8,10,12,15,16], lymph node-positive disease [3,5,10,12,15], poor Eastern Cooperative Oncology Group (ECOG) performance status [5], sarcomatoid histopathological features [5,15], advanced local tumour stage [8], concomitant perinephritic fat invasion [5,12] and Fuhrman grade [3,12] to be independent prognostic factors [5]. Bertini et al [15] showed reduced survival of patients with friable thrombus consistency compared with solid IVC thrombi.…”
Section: Discussionmentioning
confidence: 99%
“…In particular it was shown that tumor thrombus level does not predict recurrence or mortality in this group of ccRCC patients who present with IVC involvement in the renal vein (Group 1) or subdiaphragmatic IVC tumor thrombus (Group 2), in comparison to involvement of IVC above diaphragm or atrial extension (Group 3). Survival is determined by inherent aggressiveness of the cancer manifested by tumor size, grade and distant metastasis at presentation [28]. Pre-surgical treatment with sunitinib is able to ease surgery for ccRCC tumor thrombi and surgery after sunitinib treatment may be possible without additional morbidity.…”
Section: Discussionmentioning
confidence: 99%